(Invited) Probing Dopants in 2H MoS2 Crystals and 2D Layers by Electron Paramagnetic Resonance: Identification and Quantification. (16th August 2017) - Stesmans, Andre; Iacovo, Serena; Schoenaers, Ben; Houssa, Michel; Afanas'ev, Valeri V.
Abstract : Low-temperature electron spin resonance (ESR) study on the atomic nature of doping in geological p-type 2H MoS2 crystals reveals two main types of responses. The major one, of axial symmetry, stems from As acceptors, with As substituting for S, which, occurring with density ~2.4x10 17 cm -3, predominantly accounts for the p-type doping. Its ESR spectrum points to manifest non-uniform As dopant distribution, i.e., substantial clustering, with only ~13% of the As response originating from single decoupled As impurities. A second, much weaker so far unknown signal, of spin density ~5x10 14 cm -3, shows lower than axial symmetry, likely orthorhombic ( C 2v ). Based on salient ESR characteristics, it is assigned to the Pb impurity substituting for Mo, the center operating as acceptor. The dopant activation energy, Ea, was assessed through cautious monitoring of the signal intensity vs. temperature. For As, this resulted in Ea = 0.7 ± 0.2 meV, unveiling As as a noticeable shallow acceptor. The adduced insight may contribute to developing tunable, robust p-type doping strategies for few-layer MoS2 application in future nano-electronic devices.